Sustainability in Industry 4.0 Business Practice: Insights From a Multinational Technology Company - Mayer, Claude-Hélène; Oosthuizen, Rudolf M. (Frontiers in Sustainability, 2022)
Abstract Industry 4.0 (I4.0) needs new business practices, which focus on its positive impacts and sustainability. This article presents a case study from a multinational engineering company operating in South Africa and the challenges that areas managers experienced in this organisation. It further explores meaning and meaning-making in times of organisational change and transformation within the South African business context. The findings respond to questions around the I4.0 business practice and meaning-making in organisational times of change and sustainability. Themes which are identified are speed, effectivity, and Broad-Based Black Economic Empowerment (BBBEE). However, findings also indicate that emotions and the human touch are key in technologising work environments. The study further denotes that sustainable business practice requires the constant development of skills and knowledge of employees, as well as the systemic integration of the ecological environment and the care for the eco-system.